Psychological barriers to Internet usage among older adults in the UK. - Adams, Nichola
The Internet is an important tool in assisting the older population to lead independent and social lives. However, the majority of Internet users are under 55. This study investigated the following psychological barriers to Internet use by older adults : perceived usefulness, perceived ease of use, Internet efficacy, perceived complexity of navigation and perceived complexity of terminology. Twenty-three subjects (aged 55-75 years) were interviewed in the UK. The influence of age, computer and Internet experience and training on these psychological barriers were explored. The results showed that the majority of the older adults who had a positive perception of usefulness, ease of use and efficacy of the Internet or e-mail, used the Internet or e-mail more often. In addition, it was found that computer or Internet experience increased perceptions of ease of use and efficacy of the Internet and reduced perceived complexity of navigation. There was no difference between the two age groups (55-65 and 66-75 years) in these psychological barriers. It was concluded that increased marketing of the Internet (aimed at the older user), more simple and uniformly designed Internet pages, more user-friendly online help and error message terminology and increased provision of training for the older user would assist uptake of the World Wide Web.
Keywords: Older adult; Internet; Psychological barriers